(untitled) (International Journal of Engineering and Computer Science, 2017)
A Design method for the optimization of three-phase Induction Motor has been presented in this paper. The optimal design has been compared with a normal design having the same ratings. The method for optimization selected here is Genetic Algorithm(GA). Four objective functions such as Air-Gap Length(Lg), Stator Copper Loss(SCL), Rotor Copper Loss(RCL), Stator Iron Loss(SIL) are considered here. The GA method is very useful to optimize the motor performance. There are a number of non-linear equations which reflects the motor performance over here. Matlab is a powerful software used here for this NLP technique optimization.